Поліваріантність онтоморфогенезу кримського ендемічного раритетного виду Anthemis sterilis Steven (Asteraceae Bercht. et J. Presl) - Kalista, M.S.; Scherbakova, O.F.; Novosad, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
Three basic variants of ontomorphogenesis development of individuals were detected in natural populations of Anthemis sterilis Steven under condition of Karadag. According to the first variant the individuals develop faster as biennial monocarpics, and to the second and third – they develop slower as short-lived monocarpics or oligocarpics. Three periods (latent, pregenerative and generative) and 5 age states (seedlings, juvenile, immature, virginal and generative) were detected in ontomorphogenesis of species individuals of different biomorphs. In this paper the diagnostic indicators of age states are given and the generalized scheme of ontomorphogenesis was created. The phases of morphogenesis of individuals are detected. The size and morphological polyvariance of individuals of different biomorphs was ascertained. It was found that ecological and coenotic conditions of habitats have significant influence on the appearance of different types polyvariance.